Improving the heifer rearing efficiency of fully-housed dairy systems in the UK - Ross, L.H. (2023)
Whole-farm feed efficiency (WFFE) is a novel metric to measure farm performance which accounts for the costs of all animals in a dairy system, including herd replacements, dry cows, and bulls. However, our understanding of current heifer rearing practices in the UK and how they may affect WFFE is limited. This PhD thesis broadly aimed to assess the effect of factors relating to rearing herd replacements which are associated with WFFE. Using the University of Nottingham’s Centre for Dairy Science Innovation as a representative of a high-yielding (mean annual milk yield 12,780 L/cow), all-year-round system, data from Holstein-Friesian heifers born between 2007 and 2018 were used to analyse age and live weight (LW) at first calving and how they, one; are affected by calf health, two; influence first lactation performance and three; impact longevity and lifetime performance. Age at first calving (AFC) is recognised as a key performance indicator in the dairy industry, but the proportion of systems achieving the 730 day (24 month) target has remained low. In study one, mean age and maturity at first calving for the herd met industry targets but only 10% of heifers met both targets. Studies two, three and four demonstrated how rearing performance and AFC are impacted by disease, growth rate and fertility. Study two found four in ten calves contracted a gastrointestinal enteric disorder (GED) for two days between 10 and 15 days of age on average. In the first four weeks of life GED reduced milk replacer intake by 1.0 L/d (p=0.001) and daily LW gain (DLWG) by 0.14 kg/d (p=0.007) and decreased weaning LW by 10% (p<0.001). Reduced milk replacer intake and greater unrewarded visits to the automatic calf feeder were associated with GED (p<0.05) and have the potential to be developed into automated tools for early indication of disease. In study three, bovine respiratory disease (BRD) delayed AFC by 41 days (p<0.001), increasing estimated rearing costs by £708 per heifer (39%). Study four found that heifers which took more than 50 days after first service to be diagnosed pregnant had 2.4% less maturity at first service (p<0.001), took 18 days longer to conceive during first lactation (p=0.021), were 8.5% less likely to calve a second time (p=0.043) and spent 156 fewer days in milk over their lifetime (p<0.001). Study five concluded that heifers must enter the milking herd with sufficient maturity to achieve a high dry matter intake and milk yield during first lactation, but factors which increase feeding and resting time of heifers can further improve first lactation performance. Lastly, in study six, heifers calving at 700 days (23 months) conceived 22 days earlier in their first lactation (p=0.034), repaid their rearing costs 254 days sooner (p<0.001) and spent an additional 8.2% of their life lactating (p=0.003). In summary, the most efficient heifers in this herd were those that calved at 700 days with sufficient maturity and were fertile. This can be achieved by investing adequate resources into rearing heifers at target growth rates and reducing disease incidence. Costs associated with improved heifer rearing will be returned by increasing lifetime productivity of individual cows. Increasing the proportion of heifers achieving rearing targets will increase heifer rearing efficiency and indirectly improve WFFE of the herd.